CORRELATION OF TECTONICS, SEISMICITY AND GEOTHERMICS OF LESBOS ISLAND USING REMOTE SENSING DATA AND GEOGRAPHICAL INFORMATION SYSTEMS - Voulgaris, N.; Parcharidis, I.; Pahoula, M.; Pirlis, E. (Bulletin of the Geological Society of Greece, 2018)
The development of a specialized Geographical Information System aiming at the better understanding of the relation between tectonics, seismicity and geothermal potential of Lesbos Island is discussed in the present paper. The development of this system was based on the processing and analysis of satellite images in order to identify both tectonic and thermal anomalies for further correlation with available vector and raster data. For this purpose a database including topology, geology, tectonics, seismicity and geothermy, was created. This data set derived from digitizing the topographic and geological maps of HAGS and IGME, from the analysis of the satellite image and from bibliography. As a result of the data processing there were indications about new evidence concerning the tectonics and the geothermy of Lesbos Island.